INFORMATION AND COMMUNICATION DIGITAL TECHNOLOGIES AND TEACHER FORMATION IN A CONTRUCTIONIST, CONTEXTUAL AND MEANINGFUL APPROACH TO GENERATE AN INCLUSIVE SCHOOL. - Nascimento dos Santos, Danielle Aparecida do [UNESP]; Moriya Schluenzen, Elisa Tomoe [UNESP]; Schluenzen Junior, Klaus [UNESP]; Tan, DTH; Fang, LML (Ieee, 2013)
This doctoral thesis, developed within the Ambientes Potencializadores para a Inclusao (API) reseach group at the Universidade Estadual Paulista Julio de Mesquita Filho/ Faculdade de Ciencias e Tecnologia (Unesp/FCT), studies the context of teacher training under the theme axes: Use of Information and Communication Digital Technologies (Tecnologias Digitais de Informacao e Comunicacao - TDIC) in Education, Inclusive Education and Distance Education. The theoretical and methodological approach underpinning the study is Constructivist, Contextual and Meaningful (Construcionista, Contextualizada e Significativa - CCS), making use of input from the studies of Papert, Valente, Schlunzen, Almeida and others, which presuppose valuing different ways of teaching and learning by using the TDIC. These ways of teaching imply a reorganization of pedagogical practice through the development of skills and promotion of strategies where all students (including those with disabilities), have the right of access and to stay in school, learning with quality. UNESP is committed to the training of elementary school teachers and, along with the Universidade Virtual do Estado de Sao Paulo (UNIVESP), offers Degrees in Pedagogy UNIVESP / UNESP, and is currently training 1004 (one thousand and four) teachers working in basic education in the state of Sao Paulo. Held in a semipresential modality, the course curriculum is organized in modules and themes / disciplines from broad areas of undergraduate training. There are Articulator Axes in these modules and, among these, the Articulator Axis: Inclusive and Special Education - 120 hours/class (linked to Block 2: Didactic of Contents). The focus of this research is directed to the preparation and monitoring of the development of this articulator axis. The research questions are: Is it possible, in the process of training teachers in a course of semipresential Pedagogy, to guide them to work using TDIC in a CCS approach to generate an inclusive school? How does the Articulator Axis enable teachers to apply the knowledge constructed in this context? In order to answer these questions, the general goal is to analyze the process of teacher training aimed at teaching the fundamentals of Inclusive Education in a perspective of working with TDIC projects using a CCS approach. The methodological nature is of a qualitative intervention type, and the subjects of semipresential training comprise a sample of 160 students from the UNIVESP / UNESP Degree in Pedagogy and 8 guiding discipline (tutors responsible for 4 classes where students are enrolled). Analysis of preliminary data available in the Virtual Learning Environments of selected classes indicate that the discussion on curricular and teaching strategies was expanded in the development of Articulator Axis; students developed plans for inclusive education in transdisciplinary perspectives and began to look further into such issues as the use of TDIC and working with cross-cutting themes, namely, meanings attributed to theory and practice. It is expected that it will be possible to characterize the effective contributions of the proposal and the impacts of the development of inclusive education plans, by the end of the study, featuring not only an approach to teaching but also to CCS training.
Keywords: Teacher Training; Constructionist; Contextual and Meaningful Approach